An Action Research Approach to the Design and Implementation of an On-line Course in Applied Mechanics - Allinson, Anthony J. (Proceedings of the International Conference on Networked Learning, 2002)
Since the establishment of democratic government in South Africa, tertiary education has been experiencing profound changes in its structure, governance, demographics and environment. This paper describes an action research approach to the design and implementation of an on-line course in Applied Mechanics, during rapid change in structural, human and technological environments. The action research approach enabled the design to be responsive to the environmental change, and to direct the design while serving as a working example of action research for professional development. The project was carried out as part of an on-line collaborative professional development programme. It has also been valuable as a means of documenting and viewing the design.